2015
DOI: 10.1111/ijfs.12926
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and antioxidant properties of non‐refined sugarcane alternatives to white sugar

Abstract: Summary Antioxidant properties of commercial sugarcane‐derived products were analysed to study their suitability for being used as functional ingredients. Cane honey, several jaggeries and several brown sugars were selected from the market and analysed in terms of physicochemical characteristics and antioxidant properties, and compared with white refined sugar (twelve products in total). Moisture, water activity, total soluble solids, pH, colour and sugar profile are reported. As for antioxidant properties, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 42 publications
0
67
3
1
Order By: Relevance
“…The MC was determined by weight difference after vacuum drying for 24 h (65 ± 2 °C, 13 kPa) [29]. The TSS quantification was made by measuring the refractive index at 20 °C using a refractometer with electronic temperature control and conversion to Brix degrees values (Index Instruments Ltd. Model TCR [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The pH readings were done directly on the vinasse samples and diluted molasses with a digital pH-meter (Hach ® Model HQ11D).…”
Section: Physicochemical Characterization Of By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MC was determined by weight difference after vacuum drying for 24 h (65 ± 2 °C, 13 kPa) [29]. The TSS quantification was made by measuring the refractive index at 20 °C using a refractometer with electronic temperature control and conversion to Brix degrees values (Index Instruments Ltd. Model TCR [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The pH readings were done directly on the vinasse samples and diluted molasses with a digital pH-meter (Hach ® Model HQ11D).…”
Section: Physicochemical Characterization Of By-productsmentioning
confidence: 99%
“…Although multiple studies have explored some of the products and by-products derived from sugarcane processing as a source of bioactive antioxidant compounds [4,15,[17][18][19][20][21][22][23], the present study focuses on molasses and even more in vinasses since the latter are the less explored byproduct in the sugarcane industry in terms of its potential biological activity. Among the molecules that have been isolated from different matrices from sugarcane processing it is possible to find several compounds such as apigenin, luteolin, tricine, quercetin, and gallic, caffeic, chlorogenic, ferulic, vanillic, and syringic acids, among others [4,15,17,18,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in polyphenols, including flavonoids and phenolic acids, has considerably increased because several studies have demonstrated that the toxic effects of phenolic compounds depend on phenolic concentration (Guimarães et al, 2007;Payet, Sing, & A., Smadja, J, 2006;Valli et al, 2012). Numerous studies have evaluated the potential toxicity of natural sweeteners, such as honey, molasses, and syrups (Guimarães et al, 2007;Payet et al, 2006;Seguí, Calabuig-Jiménez, Betoret, & Fito, 2015;Valli et al, 2012). MRBS has been recently commercialized in Malaysia because of its antioxidant content.…”
mentioning
confidence: 99%
“…In contrast, brown sugar is a nonrefined product from sugarcane. [36] Sample AL contained 15.61 g.kg −1 glucose. Fructose was not detected in any of the samples.…”
Section: Saccharidesmentioning
confidence: 99%